2020
DOI: 10.1002/jor.24948
|View full text |Cite
|
Sign up to set email alerts
|

Diflunisal‐loaded poly(propylene sulfide) nanoparticles decrease S. aureus‐mediated bone destruction during osteomyelitis

Abstract: Osteomyelitis is a debilitating infection of bone that results in substantial morbidity. Staphylococcus aureus is the most commonly isolated pathogen causing bone infections and features an arsenal of virulence factors that contribute to bone destruction and counteract immune responses. We previously demonstrated that diflunisal, a nonsteroidal anti-inflammatory drug, decreases S. aureus-induced bone destruction during osteomyelitis when delivered locally from a resorbable drug delivery depot. However, local d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Upon parenteral administration of nanoparticles with diflunisal into mice subjected to osteomyelitis, polymer preferential distributed to infected femurs. There, owning to the inflamed milieu, PPS moiety underwent ROS-mediated oxidation, which resulted in change of core character from hydrophobic to hydrophilic and final release of diflunisal ( Ford et al, 2021 ).…”
Section: Reactive Oxygen Species-sensitive Drug Delivery Systemsmentioning
confidence: 99%
“…Upon parenteral administration of nanoparticles with diflunisal into mice subjected to osteomyelitis, polymer preferential distributed to infected femurs. There, owning to the inflamed milieu, PPS moiety underwent ROS-mediated oxidation, which resulted in change of core character from hydrophobic to hydrophilic and final release of diflunisal ( Ford et al, 2021 ).…”
Section: Reactive Oxygen Species-sensitive Drug Delivery Systemsmentioning
confidence: 99%
“…Thus, Caleb A. Ford et al [23] used diflunisal-loaded nanoparticles based on poly(propylene sulfide), which were obtained by the oil-in-water emulsion method. The authors used two methods to fabricate polymer nanoparticles: a solvent evaporation technique to improve diflunisal loading parameters and a microhydrodynamics method to enhance nanoparticle product yield (for in vivo experiments).…”
Section: Nanoparticlesmentioning
confidence: 99%
“…These authors previously demonstrated [24] that poly(propylene sulfide) nanoparticles represent a reactive oxygen species-responsive drug nanocarrier for delivery of the Gli2 inhibitor, GANT58, to the targeted metastases in bone cancer. It was discussed that poly(propylene sulfide)-based biocarriers could be degraded in the presence of high levels of reactive oxygen species (ROS) and provide drug release at the target tissues and organs [23]. The cumulative release of diflunisal from poly(propylene sulfide) nanoparticles depending on different concentrations of the oxygen-derived radicals H 2 O 2 is shown in Figure 3.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Specifically, techniques such as in vivo BLI can be used in conjunction with bacteria that have been genetically modified to express the lux operon ( e.g. , Xen strains) such that the extent of the infection can be imaged in real time. ,, Additionally, the extent of infection remaining can be evaluated at the termination of the study through removal of the material and SEM imaging of the morphology of the bacterial biofilm and CFU counts of adherent bacteria. ,,,,,,,, To evaluate the degradation of implanted materials in vivo , the material can be explanted with surrounding subcutaneous tissue at intermediate time points throughout the study and characterized for its morphology using SEM, molecular weight using gel permeation chromatography, glass transition temperature using differential scanning calorimetry, and residual weight. , …”
Section: Evaluating the Efficacy Of Biomaterials To Prevent/treat Imp...mentioning
confidence: 99%